2007
DOI: 10.1016/j.jpsychores.2006.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, depressive symptoms, and hopelessness as predictors of adverse clinical events following percutaneous coronary intervention with paclitaxel-eluting stents

Abstract: Symptoms of depression, but not fatigue, predicted adverse clinical events. Hopelessness was the most cardiotoxic symptom, associated with a more than three-fold risk of clinical events 2 years post-PCI. Screening for hopelessness may lead to the identification of high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
74
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 30 publications
10
74
1
3
Order By: Relevance
“…Not only major depressive disorders but also subclinical levels increase the risk of poor prognosis 8,9 . Different depressive symptoms may also exert differential prognostic effects 9,10 . Depression as a prognostic marker has primarily been studied post myocardial infarction (MI), although we previously showed that depressive symptoms are associated with prognosis post percutaneous coronary intervention (PCI) 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only major depressive disorders but also subclinical levels increase the risk of poor prognosis 8,9 . Different depressive symptoms may also exert differential prognostic effects 9,10 . Depression as a prognostic marker has primarily been studied post myocardial infarction (MI), although we previously showed that depressive symptoms are associated with prognosis post percutaneous coronary intervention (PCI) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Different depressive symptoms may also exert differential prognostic effects 9,10 . Depression as a prognostic marker has primarily been studied post myocardial infarction (MI), although we previously showed that depressive symptoms are associated with prognosis post percutaneous coronary intervention (PCI) 10 . Knowledge of the potential pathogenic influence of depressive symptoms in PCI patients is important for secondary prevention due to the dramatic increase and projected increase in PCI procedures worldwide 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, previous research has suggested that symptoms of hopelessness are more important than either fatigue or depression for predicting cardiovascular prognosis. 23 If this is indeed the case, then it is possible that vital exhaustion predicted cardiovascular prognosis mainly due to the inclusion of hopelessness. Further work is needed to clarify the presence or absence of such symptoms when symptoms of fatigue are reported.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible that depressive symptoms only increase cardiovascular risk once they go beyond symptoms of fatigue to symptoms more indicative of depressed mood or anhedonia, or perhaps when moving beyond depression to hopelessness. 13,23 Such a tipping point would also give interventions to improve prognosis a definite target, rather than a reduction in an overall scale score by a set number of points. While interventions have been demonstrated to reduce symptoms of depression in cardiac patients, 21,24 it is unclear which symptoms were reduced as total scale scores of non-hierarchical scales have heretofore been adopted as outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies suggesting links between particular subtypes of depression (e.g. somatic or anhedonic depression) have tended to be inconsistent [89,90], recent meta-analytic findings suggest that somatic/affective (e.g. insomnia, fatigue) rather than cognitive/affective (e.g.…”
Section: Depressionmentioning
confidence: 99%